2022
DOI: 10.1136/archdischild-2022-323910
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-year observational study of paediatric tonsillitis and tonsillectomy

Abstract: IntroductionTonsillectomy is now only indicated in the UK when specific criteria are met, as outlined by the Scottish Intercollegiate Guidelines Network (SIGN) and The National Institute for Health and Care Excellence (NICE). As a result, fewer numbers of tonsillectomy are being performed. Tonsillectomy is the primary treatment for recurrent tonsillitis; therefore, we hypothesise that acute admissions to hospital with tonsillitis and infective complications will have risen since criteria were introduced. Our a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Tonsillectomy was found to be common among school-going children who were mostly in middle school (57.9%), whereas a study conducted in Australia, by Tran AH et al, showed a high prevalence of tonsillectomy among children 5–9 years of age [ 17 ]. Around 39.2% of patients with tonsillectomy have a family income of up to 9000 SAR, suggesting a lower middle class, which is also supported by research showing that twice as many children with age <16 years belong to the lower socioeconomic class [ 11 , 18 , 19 ]. However, household income showed a weak association with tonsillectomy in many other studies [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 80%
“…Tonsillectomy was found to be common among school-going children who were mostly in middle school (57.9%), whereas a study conducted in Australia, by Tran AH et al, showed a high prevalence of tonsillectomy among children 5–9 years of age [ 17 ]. Around 39.2% of patients with tonsillectomy have a family income of up to 9000 SAR, suggesting a lower middle class, which is also supported by research showing that twice as many children with age <16 years belong to the lower socioeconomic class [ 11 , 18 , 19 ]. However, household income showed a weak association with tonsillectomy in many other studies [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 80%
“…The worldwide decline of tonsillectomy is associated with more acute admissions for tonsillitis in some countries ( 83 ). There seems to be a correlation between social deprivation and both tonsillectomy and tonsillitis; hence, lower socioeconomic groups are more effected.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this appear to be multifactorial. We also might need criteria reflecting the burden of the disease on socioeconomic factors, i.e., beyond the current approach of counting of tonsillitis episodes ( 83 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the incidence of tonsillitis and enlarged tonsil is increasing with the aggravation of environmental pollution [1]. Besides, passive smoking [2] and infectious agents use [3] may be closely associated with the development of tonsillitis.…”
Section: Introductionmentioning
confidence: 99%